Genetic diversity of Butia lallemantii Deble & Marchiori (Arecaceae) based on morphometric data from three natural populations occurring in the Pampa biome (Research, Society and Development, 2022)
Butia lallemantii Deble & Marchiori is a dwarf palm tree typical of sandy regions and sandy elevations of the Pampa biome. Presents economic potential and a great ecological importance. However, the scientific information is still insufficient to use the species in genetic improvement and conservation programs. In this sense, the objective of the study was to quantify the genetic diversity within and between populations of B. lallemantii. For this three populations were used, São Francisco de Assis (1), Manoel Viana (2) and Alegrete (3). Within each population, fruit mass (FM), longitudinal diameter of the fruit (LDF), equatorial diameter of the fruit (EDF), pyrenic mass (PM), longitudinal diameter of the pyrenic (LDP), equatorial diameter of the pyrenic (EDP) and mesocarp mass (MM) were evaluated. In the analysis between populations, besides the fruit components, plant height (PH), leaf length (LL), leaflet length (LL), number of leaflets (NFL), number of fruits per infructescence (NFI) were evaluated. The variables that contributed the most to genetic diversity within and between populations were FM, PM, and MM. There is greater genetic diversity within populations than between populations. The LDF was the variable that presented the highest values of correlations within populations and LDF and LDP were the variables with the highest values of correlations between populations. The clustering methods allow the identification of divergent populations and genotypes that can be used in breeding research and conservation of the species.